(untitled) (Journal of Comparative Social Work, 2025)
Unemployment among young people is a large and multifaceted theme in contemporary social work research in the Nordic countries, with investing in youth being a top political priority. Social work has a pivotal role in the provision of employment services, particularly for young people in disadvantageous situations. We argue that the political understanding of unemployment as a social problem, and work inclusion as the solution effectuated through universalised employment support for young people, do not always correspond to social workers’ experiences and understandings of work and inclusion. This is particularly evident in postcolonial contexts, where identity politics interfere with policies of employment support, and power asymmetries between Nordic countries become visible. We suggest that culture as complex forms of local knowledge continuously negotiated and transformed by multiple actors, is a key factor for the constitution and resolution of unemployment as a social problem. Drawing on two ethnographic cases from Greenland and the Faroe Islands, we investigate how tensions between local knowledge and governance is played out in social work on young unemployment. We show how social workers insist on unemployment as social problems that need to be solved in tensions between belonging and uprooting, traditional and modern forms of life, and through postcolonial conflicts. Addressing challenges of employment support and work inclusion in areas in the Nordic region, which have been paid less attention to in research, is of crucial importance to make improvements